(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This article discusses the importance of ethics in financial accounting practices by taking the case study of PT Indofarma, a state-owned pharmaceutical company involved in presenting financial statements that did not comply with the principles of transparency and accountability. This study aims to analyze how ethical violations occurred in the preparation of financial reports and to examine the public administrative legal aspects related to supervision and law enforcement regarding these violations. The method used in this article is a normative-juridical approach by reviewing secondary data from court decisions, audit reports, and scientific literature. The results of the study show that weak internal supervision and lack of professional integrity are the dominant factors behind ethical violations. Furthermore, this study also highlights the important role of law enforcement officials and state financial supervisory institutions in handling similar cases to maintain public trust in state-owned companies’ financial reports. By upholding professional ethics, accounting practices are expected to meet not only legality but also morality.